Imidazolium‐Based Ionic Liquids as Initiators in Ring Opening Polymerization: Ionic Conduction and Dielectric Response of End‐Functional Polycaprolactones and Their Block Copolymers. Issue 11 (18th February 2016) - Choi, U Hyeok; Mittal, Anuj; Price, Terry L.; Colby, Ralph H.; Gibson, Harry W.
Abstract : Imidazolium alcohols, [R‐Im‐Z‐OH] + [X] −, are investigated as initiators for ring opening polymerization (ROP) of ε‐caprolactone (CL). Two monomeric imidazolium alcohols {I [R = HOOC(CH2 )5, Z = (CH2 )11, X = Br] andIII [R = n‐ Bu, Z = (CH2 CH2 O)3 CH2 CH2, X = bis(trifluoromethylsulfonyl)imide (TFSI)]} are successfully utilized as initiators for ROP of CL, yielding corresponding polycaprolactones (PCL)Ia‐Br andIIIa‐TFSI . The oligoesterII derived fromI also acts as an initiator, providing block copolymerIIa‐Br . By anion exchangeIa‐Br andIIa‐Br are converted toIa‐TFSI andIIa‐TFSI . The TFSI polymers have lower glass transition temperatures ( T g ), resulting in higher conductivity, compared to the Br polymers. The ionic conductivities of the PCL block copolymers are higher than those of the PCL homopolymers, despite the similar T g, because of their higher ionic content. Their static dielectric constants ( ε s ) increase linearly with ion content and exhibit the temperature dependence expected by Onsager, in the liquid state. The semicrystalline PCL homopolymers, upon crystallization, undergo a significant increase in ε s, owing to a Maxwell–Wagner–Sillars interfacial polarization. The present results demonstrate that with proper design, block copolymers have the potential to provide high ionic conductivities combined with good mechanical strength, key attributes for application of these materials in mechanical actuators. Abstract : End‐functional polycaprolactones and their block copolymers containing ionic liquid functionalities are synthesized by ring‐opening polymerization. The ionic conductivity and dielectric constant are investigated, revealing that with proper design, block copolymers have the capacity to provide high ionic conductivity combined with good mechanical strength, key attributes for application of these materials in electroactive ionic actuators and sensors.